Venous thromboembolism does not share strong familial susceptibility with pre‐eclampsia/eclampsia: a nationwide family study in Sweden. Issue 10 (21st March 2013) - Zöller, B; Li, X; Sundquist, J; Sundquist, K
<x xml:space="preserve">Abstract</x> Objective Genetic variants associated with venous thromboembolism (VTE) have been suggested to be involved in the pathogenesis of pre‐eclampsia/eclampsia (PEC/EC). This nationwide study aimed to determine whether VTE shares familial susceptibility with PEC/EC. Design Population‐based cohort study. Setting Sweden. Sample A total of 941 841 Swedish women delivering their first child between 1987 and 2008. Methods Data from the Swedish Multigeneration Register were linked to the Swedish Hospital Discharge Register. The risk of PEC/EC was determined in primiparous women with a family history of VTE (in parents and/or siblings), compared with primiparous women without a family history of VTE. Odds ratios (ORs) were calculated by logistic regression. Main outcome measure PEC/EC in first pregnancy. Results In total, 43 621 women had PEC/EC in association with their first pregnancy. The OR for PEC/EC in women with a family history of VTE was 1.06 (95% CI 1.01–1.11); however, a family history of VTE was associated with higher odds of PEC/EC among women with previous hypertension (OR 1.38, 95% CI 1.25–1.52). Conclusion A family history of VTE is weakly associated with PEC/EC risk, and is not clinically useful for the prediction of PEC/EC. The results of the present study suggest that it is unlikely that strong disease‐causing mutations shared by VTE and PEC/EC are common in the Swedish population. The novel association between family history and PEC/EC among the subgroup with previous hypertension needs further confirmation in future studies.